Constructing minimum interference connected dominating set for multi–channel multi–radio multi–hop wireless network. (26th March 2012) - Shan, Shan; Wu, Weili; Wang, Wei; Du, Hongjie; Gao, Xiaofeng; Jiang, Ailian
Multi–hop wireless networks have no fixed physical backbone infrastructure, so Connected Dominating Set (CDS) is frequently selected as virtual backbone to improve network efficiency. Interference is a big problem which prevents wireless networks from reaching efficiency; however, previous works construct CDS as virtual backbone without consideration of interference. In this paper, we consider the problem of how to construct Minimum Interference Connected Dominating Set (MICDS) in multi–channel multi–radio multi–hop wireless networks. Multi–channel communication helps to reduce interference and improve network performance. A two–phase algorithm named MIS–colouring is presented for MICDS problem, and theoretical analysis is also given. However, due to the characteristics of the problem itself, it is quite difficult to compute the approximation ratio for MIS–colouring. Simulation results show that through proper CDS structure selection and channel assignment, MIS–colouring algorithm can minimise the total interference of CDS as a virtual backbone for multi–channel multi–radio multi–hop wireless networks.